Peran Absensi Orang Tua dan Gaya Pengasuhan terhadap Perilaku Delinkuensi Remaja dengan Kecerdasan Emosional sebagai Moderator - Adelia Hani Sabrina (Inovasi Kesehatan Global, 2025)
This study examines the influence of parental absenteeism and parenting styles on adolescent delinquent behavior, as well as the role of emotional intelligence as a moderator. The research uses a quantitative approach with a correlational design. Data were collected from 224 high school students using delinquency scales, parental absenteeism, parenting styles, and the TEIQue-SF. The data were analyzed using linear regression and moderation analysis with SPSS and the PROCESS model 1 macro. The results indicate that parental absenteeism has a significant positive effect on juvenile delinquency (β = 0.232, p < 0.01), which means that the more frequently parents are absent, the higher the likelihood of delinquent behavior in adolescents. Additionally, parenting styles also have a significant effect on delinquency (R² = 0.149, p < 0.01). Both authoritarian and permissive styles increase the risk of delinquency, while the authoritative style serves as a protective factor that can reduce juvenile delinquency. The authoritative style, combining discipline with affection, is shown to be effective in preventing negative behaviors in adolescents. Emotional intelligence plays a significant role as a moderator in the relationship between parental absenteeism and delinquency (β = -0.128, p < 0.05), suggesting that adolescents with higher emotional intelligence can mitigate the negative impact of parental absenteeism on their delinquent behavior. However, emotional intelligence does not significantly moderate the relationship between parenting styles and delinquency. These findings highlight the importance of active parental involvement in parenting and the development of adolescents' emotional intelligence to prevent delinquent behavior. Therefore, comprehensive and culturally-based intervention approaches involving families, schools, and communities are needed to support the prevention of adolescent delinquency and foster healthy, positive relationships for them.